Environmental DNA as a tool for hydropower impact assessments: current status, special considerations, and future integration - Moody, Kristine N.; Gardner, Steven T.; Sundt‐Hansen, Line E.; Fossøy, Frode; McCoskey, Dana N.; Morrice, Katherine J.; Pracheil, Brenda M. (Biological reviews of the Cambridge Philosophical Society, 2025)
Globally there is an urgent need to find sustainable solutions to balance energy production with the protection of vulnerable species and conservation of biodiversity. This is particularly critical for freshwater ecosystems, habitats, and species that may be impacted by hydropower development and operations needed to meet energy grid demands. Reliable and accurate environmental impact assessments (EIAs) that identify the biological, physical, or social impacts of hydropower are key to ensure biodiversity, ecosystem, and societal sustainability. The analysis of environmental DNA (eDNA) has the potential to transform hydropower EIAs, management and mitigation planning, and decision‐making procedures. Further, the incorporation of eDNA surveys into EIAs during both hydropower planning and continued operations may streamline regulatory processes by improving our understanding of potentially impacted biota and habitats and evaluating environmental impacts mitigation. Here, we: ( i ) highlight current understanding and use of eDNA in freshwater environments; ( ii ) examine critical considerations for eDNA integration into hydropower EIAs and biological monitoring; ( iii ) identify knowledge gaps in eDNA analysis and applications unique to hydropower‐regulated systems; and ( iv ) discuss future opportunities to bolster the incorporation of eDNA into hydropower research including regulatory acceptance and public engagement. While we acknowledge that there are several factors that may complicate the broad adoption of eDNA as a tool for assessing the impacts of hydropower, we anticipate that growing confidence in eDNA through hydropower‐specific protocols, calibrations, and validations will overcome these inherent uncertainties.